KETERAMPILAN MANAJERIAL KEPALA SEKOLAH TERHADAP KOMITMEN KERJA GURU SMK - Rahmawati, Ima; Nur Aida, Siti; Lestari, Hana; Ihsan, Muzhir (JURNAL KAJIAN ISLAM MODERN, 2025)
This study aims to analyze the influence of school principals' managerial skills on teachers' work commitment in vocational high schools (SMK) accredited with a "B" in Pamijahan District, Bogor. The research is quantitative in nature, using a survey method conducted through interviews, documentation, and the distribution of questionnaires to 56 respondents, who are teachers in these schools. The sampling technique used is non-probability sampling with a total sampling approach. Data collection was carried out by distributing questionnaires that included indicators of managerial skills and teachers' work commitment. The collected data were then analyzed using simple linear regression to test the impact of managerial skills on teachers' work commitment. The results of the study indicate that the school principals' managerial skills have a positive and significant influence on teachers' work commitment. The regression analysis resulted in the equation Y = 40.441 + 0.582X, with a t-value of 5.382, which is greater than the t-table value (2.395), and a p-value of 0.000, which is smaller than α = 0.01, indicating a significant effect of managerial skills on teachers' work commitment. Based on these findings, it is recommended that school principals develop their managerial skills, particularly in planning, organizing, and effective communication, to enhance teachers' work commitment. Furthermore, it is suggested that the local education office provide further training for school principals in managerial skills to create a more conducive work environment for teachers.